2004
DOI: 10.1149/1.1805519
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Potential-Dependent Stages in OH[sub ads] Formation on the Pt[sub 3]Cr Alloy (111) Surface

Abstract: Results of a periodic spin-density-functional theory study of the electronic structure and the local adsorption properties of the Pt 3 Cr(111) alloy surface are presented. A slab composed of four-atom-layer is used to model the ͑111͒ surface of the L1 2 bulk phase with the two topmost layers and adsorbed species allowed to relax. Adsorption energies for OH and H 2 O have been calculated as functions of initial OH coverage. Using these energies in a model based on reaction energies for acid electrolyte, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 62 publications
(116 reference statements)
6
48
0
Order By: Relevance
“…Oxygen reduction on various cathode materials (metals [118][119][120][121][122][123][124][125][126] and metal oxides [116]) have been studied using either cluster or periodic slab models. In this section, we will review DFT calculations of oxygen reduction on electrode and electrolyte surfaces (2PBs and TPBs) to gain more insight into the reaction sequence of oxygen reduction.…”
Section: Investigations Into Oxygen Reduction Mechanismsmentioning
confidence: 99%
“…Oxygen reduction on various cathode materials (metals [118][119][120][121][122][123][124][125][126] and metal oxides [116]) have been studied using either cluster or periodic slab models. In this section, we will review DFT calculations of oxygen reduction on electrode and electrolyte surfaces (2PBs and TPBs) to gain more insight into the reaction sequence of oxygen reduction.…”
Section: Investigations Into Oxygen Reduction Mechanismsmentioning
confidence: 99%
“…The energetics of the dissociated components (O ad and OH ad ) also significantly influence the over-all reaction as it dictates subsequent reaction steps such as protonation [3,4] and oxidation of other surface species such as CO [5,6]. However, most of the fundamental surface science studies are devoted to the understanding of O and OH adsorption on metal or alloy catalysts [7][8][9][10], which are generally much simpler to treat. The challenge posed by a more complex OOH adsorption hinders both electrochemical and surface science studies.…”
Section: Introductionmentioning
confidence: 99%
“…Currently experimental [45][46][47][48] and computational [49][50][51][52] studies agree that the lowest physisorbed state for molecular oxygen is along the Pt-Pt bond. However most computation find an adsorption of around 0.7eV, whereas the experimental results are 0.38eV [47] and 0.5eV, although Ohma et al in 2010 found a binding energy of 0.39eV using DFT.…”
Section: Interaction With Oxygen Moleculementioning
confidence: 90%
“…There is also agreement on the binding energy of water on a plane (111) surface, but there is no such consensus for the binding energy of water on a Pt cluster. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Oxygen adsorption on Pt 111 has also been studied, both experimentally [45][46][47][48] and computationally [49][50][51][52], and it is found that oxygen can be in many different states. Chemisorbed molecular oxygen can be in both paramagnetic (top-bridge-top) and nonmagnetic state (tilted bridge on the fcc and hcp sites).…”
Section: De-ee0000466 Ballard Materials Products Incmentioning
confidence: 99%